Alterações morfofuncionais e bioquímicas do músculo vasto lateral de pessoas com COVID longa - Antão, Rosangela Aline (Universidade Federal de São Carlos, 2025)
Muscle symptoms are common and disabling complaints in Long COVID, however, their pathophysiology remains to be elucidated. Two main hypotheses have been proposed: a local and persistent viral infection or the effects of chronic systemic inflammation. To test these hypotheses, biopsies of the vastus lateralis muscle from individuals with Long COVID and healthy controls were analyzed using Western Blot, immunofluorescence and functional analyses. The results refuted the local infection hypothesis: there was no increase in Spike protein or ACE2 receptor antigens, and the pro-viral protease TMPRSS2 was decreased (p < 0.05). The immune profile was atypical, with a decrease in macrophages (p < 0.05) and no change in T lymphocytes, suggesting immune dysregulation rather than classic cellular inflammation. This dysregulation was associated with tissue remodeling, including selective atrophy of type I and IIA fibers and an unexpected decrease in collagen content (p < 0.05). Functionally, the tissue showed a profound deficit at the cellular level, with a significant reduction in single fiber strength (p < 0.05), a finding not detected in global strength tests. Taken together, these results suggest that muscle pathology in Long COVID is not caused by direct viral damage, but rather by inflammatory and immune dysregulation that leads to atrophy, matrix remodeling and contractile dysfunction at the cellular level.
Morphofunctional and biochemical changes in the vastus lateralis muscle of people with long COVID
Keywords: COVID longa; SARS-CoV-2; Sintomas musculares; Disfunção; Inflamação; CIENCIAS BIOLOGICAS::FISIOLOGIA